Application of Wahdatul Ulum in Community Service - Muhammadyunus; Bima Rizky Ananda; Muhammad hafizd; Muhammad Luthfi; Ilham nur Hasibuan (ISNU Sumatera Utara, 2024)
This study aims to analyze the implementation of the Wahdatul Ulum concept in community service and its impact on community welfare. Using a qualitative descriptive method, data were collected through in-depth interviews with program implementers and direct observation of community service activities in Baru Village, Batang Kuis. The results of the study indicate that the integration of various disciplines in community service programs produces more targeted solutions and increases the effectiveness of activities. Programs that implement the Wahdatul Ulum approach have proven successful in increasing community access to education and health services, as well as encouraging active community participation in social activities. Although there are challenges in understanding and communicating this concept, the implementation of Wahdatul Ulum has great potential to shape positive social change. This study recommends increasing the capacity of implementers through training and outreach to the community to maximize the effectiveness of community service programs.